From movement to mood: the exploration of the relationship between adolescents' 24-hour movement behaviors and subjective well-being - Haohong Ye; Dongting Yun; Xiaoyue Ji; Yue Qiu; Chenggeng Li; Jia Zheng (Acta Psychologica)
In light of the limited research concerning how movement behaviors collectively influence the subjective well-being of Chinese adolescents, as well as the lack of customized 24-hour movement guidelines, this cross-sectional study investigates the association between adolescents' adherence to these guidelines and their subjective well-being. Specifically, it delves into the mediating roles of screen time (ST) and sleep duration (SLP) in the connection between moderate-to-vigorous physical activity (MVPA) and subjective well-being. By distributing paper-based questionnaires assessing movement behaviors and the subjective well-being ladder scale to middle schools, we collected valid cross-sectional data from 616 adolescents aged 13 to 17 years (mean age = 14.86 years, 43.4 % males) in southwest China. The findings indicate that adhering to the MVPA guideline alone shows no significant association with subjective well-being, whereas adhering to the guidelines for ST, SLP and combinations of these guidelines shows a significant positive relationship with individuals' subjective well-being. Furthermore, the number of 24-hour movement guidelines adhered to (1, 2, or 3) is significantly associated with subjective well-being. Importantly, MVPA is directly associated with subjective well-being and also does so indirectly via the mediating roles of ST and SLP. In the future, health promotion strategies and intervention measures should be established for adolescents' 24-hour movement behaviors, aiming to boosting their physical activity, reducing sedentary time, ensuring adequate sleep, and ultimately enhancing their subjective well-being.